2013
DOI: 10.2478/intox-2013-0001
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of rabbit muscle sarcoplasmic reticulum Ca2+-ATPase activity by novel quercetin derivatives

Abstract: Sarcoplasmic reticulum Ca2+-ATPase (SERCA) is the pump crucial for calcium homeostasis and its impairment results in pathologies such as myopathy, heart failure or diabetes. Modulation of SERCA activity may represent an approach to the therapy of diseases with SERCA impairment involvment. Quercetin is flavonoid known to modulate SERCA activity. We examined the effect of nine novel quercetin derivatives on the activity of the pump. We found that 5-morpholinohydroxypoxyquercetin, di(prenylferuoyl)quercetin, di(d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Alternatively, the action of quercetin on the forskolin-stimulated Isc might be by downregulating the Na + , K + -ATPase. Indeed, Mezesova et al [ 40 ] have reported that treatment with quercetin (20 mg · kg −1 · day −1 ) in both normotensive and hypertensive rats produces impairment in the affinity of Na + binding site of the Na + , K + -ATPase like the inhibitory action on Ca 2+ -ATPase [ 41 , 42 ]. On the other hand, myricetin showed no inhibitory action but stimulatory action on Isc, suggesting that myricetin would not inhibit NKCC or produce impairment in the affinity of Na + binding site of the Na + , K + -ATPase unlike quercetin.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the action of quercetin on the forskolin-stimulated Isc might be by downregulating the Na + , K + -ATPase. Indeed, Mezesova et al [ 40 ] have reported that treatment with quercetin (20 mg · kg −1 · day −1 ) in both normotensive and hypertensive rats produces impairment in the affinity of Na + binding site of the Na + , K + -ATPase like the inhibitory action on Ca 2+ -ATPase [ 41 , 42 ]. On the other hand, myricetin showed no inhibitory action but stimulatory action on Isc, suggesting that myricetin would not inhibit NKCC or produce impairment in the affinity of Na + binding site of the Na + , K + -ATPase unlike quercetin.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, methods for the preparation of quercetin metabolites have also been developed [5], [6]. The quercetin derivatives synthesized to date include, for instance, esters of quercetin and of various aliphatic [7], [8] and aromatic carboxylic acids [9], [10], [11], quercetin-amino acid conjugates with amino acids attached to quercetin via a carbamate linkage [12], esters of sulfuric acid (i.e. quercetin sulfates) [13], [14], glycosides [15], glucuronides [5], methyl ethers [16], etc.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common flavonoids in human diet is quercetin (3,3′,4′,5,7‐pentahydroxyflavone), which occurs in nature in several different chemical forms . It has multiple biological effects such as excellent radical scavenging activity , anti‐inflammatory and relaxation of vascular smooth muscle . Quercetin pre‐treatment protected against myocardium ischaemia–reperfusion injury by decreasing oxidative stress, repressing inflammatory cascades and inhibiting apoptosis in vivo .…”
mentioning
confidence: 99%